Existence of entomopathogen fungi, Beauveria bassiana as an endophyte in cacao seedlings - Endang Sulistyowati; Febrilia Nur AINI (Indonesian Coffee and Cocoa Research Institute, 2015)
Beauveria bassiana is one of the entomopathogen fungi which is known as biological control agent of cocoa pod borer and cocoa mirids (Helopeltis spp.). Because of its effectiveness in the fields is still not consistent, so we conduct a research with the objective to know the possibility of Beauveria bassiana to be established as a endophyte. Various fungal entomopathogens have already been reported as endophytes and the various methods used to inoculate the plants with B. bassiana were partially effective. The research has been conducted in laboratory of Plant Protection, Indonesian Coffee and Cocoa Research Institute by inoculating of cocoa seeds and cocoa nursery with B. bassiana suspension. The trial was arranged by randomized complete block design with a factorial arrangement. The factor were spore concentration of B. bassiana (0; 2; and 4 g/ 10 l) and cocoa varieties (family of ICS 60, TSH858, and hybrid). The trial were use four replications. The results showed that the fungal entomopathogen B. bassiana was established as an endophyte in cocoa seedling, both from cocoa seeds and nursery application. Percentage of existence of B. bassiana colonies as endophytes one month after seeds application were ICS 60 amounted to 93.3 % both on concentration treatments, while the families of TSH 858 by 80 % and 86.67 % respectively in 2 g and 4 g per 10 l of B. bassiana spores concentration treament.. The lowest percentage was in hybrids, which amounted to 66.67% and 50%. B. bassiana colonies was exixtence as an endophyte in culture from root, stem and leaves of cocoa seedling up to 5 months post inoculation. While the application on nursery by soil drenshing, leaf spraying, and stem injection , it was known that B. bassiana colonies were found in the tissues of leaves, stems, and roots until two months after application. Colonies of B. bassiana as endophytes still exsist until six weeks after nursery was planted in the field.